w2/3+w4/3=16/3

Simple and best practice solution for w2/3+w4/3=16/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w2/3+w4/3=16/3 equation:


w in (-oo:+oo)

(w^4)/3+(w^2)/3 = 16/3 // - 16/3

(w^4)/3+(w^2)/3-(16/3) = 0

(w^4)/3+(w^2)/3-16/3 = 0

1/3*w^4+1/3*w^2-16/3 = 0

t_1 = w^2

1/3*t_1^2+1/3*t_1^1-16/3 = 0

1/3*t_1^2+1/3*t_1-16/3 = 0

DELTA = (1/3)^2-(-16/3*1/3*4)

DELTA = 65/9

DELTA > 0

t_1 = ((65/9)^(1/2)-1/3)/(1/3*2) or t_1 = (-(65/9)^(1/2)-1/3)/(1/3*2)

t_1 = 3/2*((65/9)^(1/2)-1/3) or t_1 = -3/2*((65/9)^(1/2)+1/3)

t_1 = -3/2*((65/9)^(1/2)+1/3)

w^2-(-3/2*((65/9)^(1/2)+1/3)) = 0

w^2+3/2*((65/9)^(1/2)+1/3) = 0

1*w^2 = -(3/2*((65/9)^(1/2)+1/3)) // : 1

w^2 = -3/2*((65/9)^(1/2)+1/3)

t_1 = 3/2*((65/9)^(1/2)-1/3)

w^2-(3/2*((65/9)^(1/2)-1/3)) = 0

w^2-3/2*((65/9)^(1/2)-1/3) = 0

1*w^2 = -(-3/2*((65/9)^(1/2)-1/3)) // : 1

w^2 = 3/2*((65/9)^(1/2)-1/3)

w^2 = 3/2*((65/9)^(1/2)-1/3) // ^ 1/2

abs(w) = (3/2)^(1/2)*((65/9)^(1/2)-1/3)^(1/2)

w = (3/2)^(1/2)*((65/9)^(1/2)-1/3)^(1/2) or w = -((3/2)^(1/2)*((65/9)^(1/2)-1/3)^(1/2))

w in { (3/2)^(1/2)*((65/9)^(1/2)-1/3)^(1/2), -((3/2)^(1/2)*((65/9)^(1/2)-1/3)^(1/2)) }

See similar equations:

| 4x^2+4-22=0 | | 1225+6x=1700 | | -20+19= | | 1/3z=5 | | 4/2x+20=22 | | 1225+6x=700 | | 5x-17=2x+13 | | 5x^2=12 | | -1=6y-11 | | 5/13x=25 | | 4x-7(3-3x)-9=x | | 7x+7=3x-5 | | 3m-6n=9n+12 | | -b+17= | | 3x-4y+8=26 | | 7+3t=(6-t)/2 | | a^2+3x=2a^2 | | -3(v-3)=3v-33 | | 12x=3y+6 | | -6a(-5)(2b)= | | 2x+3=57 | | 5(r-3)-2r=-30 | | Y-5=mx-2 | | 5t+3=-12 | | -10b+3(-1+b)= | | 8x-5/12=13/18 | | 8(7-p)-8=-16 | | 4x-18+8x=7x+3x+8 | | -3+n=6n+22 | | 3(x-2)=5x+4 | | 1/3x+15=20 | | 4x-2+5x+10+2x+14=0 |

Equations solver categories